2020
DOI: 10.1007/s00170-020-05630-1
|View full text |Cite
|
Sign up to set email alerts
|

Back stress and strength contributions evolution of a heterogeneous austenitic stainless steel obtained after one pass by equal channel angular sheet extrusion (ECASE)

Abstract: This research work studies the different strength contributions of a sheet-shaped heterogeneous austenitic stainless steel, after having been processed at room temperature by one ECASE pass.A significant hardness increase was found throughout its thickness, showing higher values near the edges while the middle area presents the smallest gains. The material heterogeneity gives rise to a plastic gradient deformation between the soft and hard areas of the microstructure. As a consequence, a more significant amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…This behavior is related to the heterogeneous grouping of GND between the two phases and the twinning hardening, confirming the back-stress effect indicated in Fig. 8 (i.e., more GNDs piled up on the soft than the hard phase), which has been reported in materials with two phases and with heterogeneous structures of the harmonic type where there is additional hardening by the hetero-deformation [70,71]. Furthermore, finding different microstructural and mechanical behaviors between the two phases is well related to the slip activity indicated in Fig.…”
Section: Hardening Contributionssupporting
confidence: 82%
“…This behavior is related to the heterogeneous grouping of GND between the two phases and the twinning hardening, confirming the back-stress effect indicated in Fig. 8 (i.e., more GNDs piled up on the soft than the hard phase), which has been reported in materials with two phases and with heterogeneous structures of the harmonic type where there is additional hardening by the hetero-deformation [70,71]. Furthermore, finding different microstructural and mechanical behaviors between the two phases is well related to the slip activity indicated in Fig.…”
Section: Hardening Contributionssupporting
confidence: 82%
“…While in the direction parallel to the BD, the behavior is more homogeneous (i.e., a smaller number of peaks and valleys). It has been shown that the existence of plastic gradients is related to the improvement in the ductility of metallic materials due to the combination of zones of greater hardness with more ductile zones [40][41][42]. Therefore, these gradients' formation confirms the better mechanical response in the radial direction than in the longitudinal direction, as indicated in Fig.…”
Section: Influence Of Plastic Gradients On the Tensile Responsementioning
confidence: 79%
“…In this way, ASR processing gives rise to plastic gradients' formation combining soft and hard areas in the same material. The existence of plastic gradients in metallic materials has been associated with a good combination of mechanical properties such as strength, ductility, formability, and localized hardness [21,23,44]. In this way, the GNDs distributions indicate that the ASR process induces a greater curvature on the material's microstructure, giving rise to a better strain hardening capacity in the IF steel than the CR process.…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…On the other hand, the large presence of GNDs at the edges of the sheet corroborates the texture changes since this type of dislocation represents different sliding behaviors in various regions of the microstructure. From the mechanical point of view, the heterogeneous distribution of GNDs induces an additional hardening mechanism in the material due to the interaction of tougher areas with softer ones, giving rise to hardening by back-stress [21,45].…”
Section: Microstructure Characterizationmentioning
confidence: 99%
See 1 more Smart Citation